APPLICATION OF ICE BREAKING ACTIVITIES TO INCREASE LEARNING MOTIVATION OF ENGINEERING STUDENTS IN SPORTS COURSES - Raditya Pratama; Via Diah Rohmana (Four Son Scholarship, 2024)
This research is motivated by the findings of a lecturer teaching sports courses at the engineering study program of Cipta Wacan Christian University in Malang who reported low student enthusiasm during class learning. This raises the need for innovative methods to increase student learning motivation. This study aims to identify the effect of the application of ice breaking on learning motivation and student activity in learning sports courses in the classroom. The method used is quantitative research with descriptive design. Data were collected through observation, interviews, questionnaires, and the internet, with a sample of 45 students consisting of 21 Civil Engineering students and 24 Mechanical Engineering students. The results showed that the application of ice breaking had a significant impact on student learning activities, with the results of data analysis showing an interval score of 63-84, which reflected a very good level of success. Students become more motivated, and learning activities increase. In conclusion, the application of ice breaking in learning sports courses can effectively increase student motivation and learning activities, making it a relevant strategy to be implemented in the Engineering study program